(Un)affirming assimilation: depictions of dis/ability in health textbooks. Issue 3 (30th November 2020) - Deckman, Sherry L.; Fulmer, Ellie Fitts; Kirby, Keely; Hoover, Katharine; Mackall, Abena Subira
Abstract : Purpose: In light of the systemic and pervasive nature of ableism and how ableist ideology structures – or limits – educational opportunities, this paper aims to contribute to the ongoing conversation within the field of multicultural education regarding how to meaningfully include dis/ability in K-12 curricula. Design/methodology/approach: This paper explores how elementary and middle school health textbooks from two prominent publishers in the USA portray dis/ability through quantitative and qualitative content analysis methods of 1, 468 images across texts. Findings: Findings indicate that the majority of the textbook portrayals of dis/ability tacitly forward assimilationist ideals. Specifically, the textbooks assume and speak to a normatively-abled reader, pointing out those with dis/abilities as different from the reader. Additionally, mainstream or normative markers are provided as evidence of success and those with dis/abilities who have been successful as such are positioned as overcoming their limitations. Practical implications: Such portrayals stifle the possibility of social transformation by reinforcing and privileging dominant, ableist views. Therefore, teachers are recommended to take steps that might counter such messages in curricular materials and teacher educators are called on to support these efforts. Originality/value: This paper extends the tradition of curricular analysis as one of the first studies to examine the portrayals of dis/ability in US health textbooks and offer practical implications for educators.